Research of the Dynamic Load Sharing of Heavy Load Planetary Gear System with Multi- floating Component - Xu Xiangyang; 2Yang Wang; Diao Peng; Tao Youchuan (Jixie chuandong)
To study the influence of multi- floating components on the load sharing of heavy load planetary gear system,taking a large wind power planetary gear system as the research object. The FE model of this system is established to analyze the load sharing. The load sharing change trend of the planetary gear with the change of planet carrier stiffness,planet gear error and the floating of the sun gear and the planet carrier,external load are analyzed. The results demonstrate that the load sharing of the system is better in the case of the floating sun and planets gear carrier at the same time. Reducing the stiffness of the floating support or increasing input load can effectively improve the load sharing capacity. The experimental verification of load sharing situation of multi- floating component planetary gear system under the change of external load and planet carrier support stiffness is carried out on the load sharing test platform.